Influence of High Milk Feeding Practices on Faecal Consistency Score and Behaviour of Early Weaned Crossbred Calves (Indian Journal of Animal Production and Management, 2024)
This study investigated the impact of high  milk feeding on the body weight of 25 early-weaned  crossbred (HF×K) calves at Livestock Research  Station, Kamdhenu University, Anand, Gujarat,  over 182 days. Calves were divided into five  treatment groups with equal numbers of male and  female calves. Colostrum was provided for the first  3 days, followed by 4 liters of fresh milk daily for the  first two weeks. The total milk quantity offered in T1,  T2, T3, T4 and T5 was 252, 329, 353.5, 378, 402.5  kg respectively, to study the faecal consistency and  behavior of calves. The faecal consistency and  behaviour of calves after one hour during morning  milk feeding was observed among the experimental  calves for milk feeding of 63 days. The observation  shown that calves of T5 group (higher quantity of  milk feeding) defecate less normal faeces with  incidences of water faeces. The calves of T5 group  exhibited discomfort sign like; standing up/down,  licking and kicking of abdomen after ingesting milk.  The high quantity of milk feeding at a stretch (T5)  caused behavior abnormality and loose faeces in  calves. The feeding of high amount of (T5) is not  advisable for the welfare and intestinal health of  crossbred calves.
Keywords: high milk feeding; crossbred calves; faecal consistency; behaviour